2020
DOI: 10.1186/s12937-020-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between healthy lifestyle score and breast cancer

Abstract: Background: Majority of earlier studies have assessed the association between individual lifestyle factors and the risk of breast cancer (BC); however, limited information is available linking the whole lifestyle factors to BC. We aimed to examine the association between combined lifestyle score (diet, physical activity (PA) and smoking) and risk of BC in Iranian population. Methods: This population-based case-control study included 350 newly diagnosed cases of BC and 700 healthy controls randomly selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
0
33
1
Order By: Relevance
“…In contrast to our finding, the results of recent case-control studies conducted in Iran indicated that HEI-2010 score was inversely associated with lower BC incidence in premenopausal (Sedaghat et al, 2018) and postmenopausal (Ghosn et al, 2020) women. However, they used the older version of HEI (HEI-2010) to assessment of dietary quality.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our finding, the results of recent case-control studies conducted in Iran indicated that HEI-2010 score was inversely associated with lower BC incidence in premenopausal (Sedaghat et al, 2018) and postmenopausal (Ghosn et al, 2020) women. However, they used the older version of HEI (HEI-2010) to assessment of dietary quality.…”
Section: Discussioncontrasting
confidence: 99%
“…Several researches have conducted to investigate the association of dietary quality and BC risk but their findings are still controversial (Kojima et al, 2017;Cade et al, 2011;Previato et al, 2015;Shahril et al, 2013;Dela Cruz et al, 2020;Ghosn et al, 2020;Petimar et al, 2019;Sedaghat et al, 2018). A cohort of 33,731 British women proposed that WHO HDI and Mediterranean dietary pattern were not associated with the risk of BC (Cade et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to a healthy lifestyle, there are some differences regarding its operationalization [4][5][6][7][8][9][10][11]. However, all cited researches consider physical activity as a part of a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…A healthy lifestyle is classified into two categories [14], which are non-modified (age, family history) and modified (no obesity, healthy diet, physical activity and no smoking) variables that contribute to having a longer life with good health [13], [15]. This study utilised modified variables to measure user's emotion for lifestyle intervention compliance including food and nutrition intake.…”
Section: A Non-communicable Diseasesmentioning
confidence: 99%